2021
DOI: 10.3389/fcell.2021.699263
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal and Functional Heterogeneity of Hematopoietic Stem Cell-Competent Hemogenic Endothelial Cells in Mouse Embryos

Abstract: Hematopoietic stem cells (HSCs) are derived from hemogenic endothelial cells (HECs) during embryogenesis. The HSC-primed HECs increased to the peak at embryonic day (E) 10 and have been efficiently captured by the marker combination CD41–CD43–CD45–CD31+CD201+Kit+CD44+ (PK44) in the aorta-gonad-mesonephros (AGM) region of mouse embryos most recently. In the present study, we investigated the spatiotemporal and functional heterogeneity of PK44 cells around the time of emergence of HSCs. First, PK44 cells in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Accordingly, CXCR4 lineage tracing has been recently used to mark a contribution of intra-but not extra-embryonic HE to innate lymphoid cells [40] and HSC-derived monocytes from microglia and other tissue-resident macrophages (TRM) [41]. Recently, some markers enriched in the YS HE have also been identified, such as Stab2 and Lyve1 [42,43], although the latter was shown not to be exclusively expressed in the YS [44]. These data support the concept that HE cells are already "primed" to become specific types of stem or progenitor cells when they are still undergoing EHT.…”
Section: Heterogeneity Of the Hemogenic Endotheliummentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, CXCR4 lineage tracing has been recently used to mark a contribution of intra-but not extra-embryonic HE to innate lymphoid cells [40] and HSC-derived monocytes from microglia and other tissue-resident macrophages (TRM) [41]. Recently, some markers enriched in the YS HE have also been identified, such as Stab2 and Lyve1 [42,43], although the latter was shown not to be exclusively expressed in the YS [44]. These data support the concept that HE cells are already "primed" to become specific types of stem or progenitor cells when they are still undergoing EHT.…”
Section: Heterogeneity Of the Hemogenic Endotheliummentioning
confidence: 99%
“…Notch pathway dependence [45][46][47] Arterial identity dependence (Lymphoid potential) [48][49][50] WNT canonical pathway dependence [31] Cxcr4 expression (Lymphoid potential) [40] Lyve1 expression Low [42][43][44] Hlf expression (until E10.5) [57] Blood flow dependence [51][52][53][54][55][56] Hypoxia/glycolysis Decrease of hematopoietic output Increase of hematopoietic output [55] Many studies have very recently employed scRNA-Seq and newer variants of this technique such as spatial transcriptomics to delve deeper into the study of the molecular determinants of EHT and to gain insight into the cellular and molecular heterogeneity of HE [39,[58][59][60][61][62][63][64], mostly in animal models but some also in human [65,66]. These studies mainly focused on intra-embryonic EHT because of its obvious connection with HSC generation, and collectively highlighted how (pro-/pre-)HSC development proceeds in a fairly asynchronous way, with cells at different stages of maturation coexisting in the same embryo.…”
Section: Hsc-and Lymphoid-competent He Emp-competent He Referencesmentioning
confidence: 99%
“… 7 , 8 , 34 Using an index-sorting strategy that can record the expression levels of multiple proteins of each sorted cell, the endothelial-biased population in PK44 cells can be further enriched by the marker combination of CD93 hi Kit lo or CD146 hi Kit lo , while the hematopoietic-biased population can be enriched by CD93 lo Kit hi or CD146 lo Kit hi . 34 …”
Section: Transcriptomic Immunophenotypic and Functional Identificatio...mentioning
confidence: 99%
“…Notably, more CD45 + hematopoietic cells were generated (Figure 4G,H) along with immunophenotypic HSPCs and hematopoietic progenitors, as detected by the CFU-C In our previous studies, HECs represented by PK44 population have been transcriptomically and functionally proven to have initiated their intrinsic hemogenic program featured by Runx1 expression and present a continuum of cellular states from endothelial-biased characteristics to hematopoietic-biased characteristics prior to acquiring hematopoietic function. [25,28,40] To determine whether the proportion of cells with blood-forming capacity was increased in PK44-represented HECs, or if the hemogenic capacity of individual blood-forming cells was enhanced, or both, we performed single HEC induction and functional assays. First, 31.3% (31/99) of cKO PK44 cells gave rise to hematopoietic progenies, unlike only the 17.5% (24/137) of the controls, indicating a 1.8-fold increase (Figure 4L).…”
Section: Loss Of Nupr1 Facilitates Blood-forming Capacity Of Hecsmentioning
confidence: 99%
“…These HSC‐primed HECs peak at E10.0 and can be efficiently captured by the surface marker combination PK44 (CD41 − CD43 − CD45 − CD31 + CD201 + Kit + CD44 + ) based on single‐cell transcriptomic prediction and functional validation. [ 25,28 ] By comparison with other endothelial and CD45 − hematopoietic cell populations around the same developmental stages, a total of 11 signature genes of HSC‐primed HECs have been identified, including the well‐known HEC marker gene Gfi1 and others such as Neurl3 and Nupr1 , the implication of which remains largely unknown. By further constructing a Neurl3‐EGFP reporter mouse model, we revealed that Neurl3 expression effectively enriched HSC‐primed HECs.…”
Section: Introductionmentioning
confidence: 99%